Diseño de la red de campus para el Gobierno Autónomo Descentralizado Municipal de Otavalo - Montes Días, Carolina Liseth (2016)
This work presents the design of the Municipal Campus Network GAD Otavalo, for which the design methodology PPDIOO (Preparation, Planning, Design, Implementation, Operation and Optimization) network is used; this project will focus only on the first three phases which are: Preparation, Planning and Design. To start the project gathering information on the current status and own network requirements is done, analyzing teams currently use, applications required by users, existing technical documentation is collected to verify the shortcomings. Later the design campus network based on the collected requirements of the municipality is made, the design is based on a system called Core Collapsed because today the teams have common characteristics of the different layers as possible as to eliminate the distribution layer and thus less money will be invested with implementation. It consists of a simulation by a specialist to verify functionality of the design software. Finally a cost analysis of investment is made, including study of brands of equipment needed for future deployment and investment study whether it is feasible or not. With this design several benefits as a secure, scalable, functional, adaptable and easily managed network is achieved is obtained. It also helps with saving time and money on external users, the speed of information is faster and safer, space is optimized and saves resources.